Respuesta :

Answer:

To solve for r in the equation -5r = -3r + 6, we need to isolate the variable r.

Here are the steps to solve this equation:

Step 1: Begin by simplifying both sides of the equation. Add 3r to both sides to eliminate the -3r term on the right side of the equation:

-5r + 3r = -3r + 3r + 6

Simplifying this gives us:

-2r = 6

Step 2: Divide both sides of the equation by -2 to isolate r. This will give us the value of r:

(-2r) / -2 = 6 / -2

Simplifying this gives us:

r = -3

Therefore, the solution to the equation -5r = -3r + 6 is r = -3.

Step-by-step explanation:

Answer: r = -3

Step-by-step explanation:

First, subtract βˆ’3r from both sides (-5r + 3r = 6)

Combine like terms on the left side (-2r = 6)

divide both sides by βˆ’2 to solve for r (r = 6/-2)

Simplify that fraction (-3)